Evaluation Of Medication Errors In The Prescribing Phase Outpatients With Acute Respiratory Tract Infections At The X Health Center In East Lampung In 2025 - Anna Aufa Nurrohmah; Nurma Suri; Ervina Damayanti; Yulianasari Pulungan (Journal of Pharmaceutical and Natural Resources, 2025)
Medication errors are considered as avoidable or preventable events which can lead to inappropriate medication use, potentially detrimental to the patient's condition, and it can occur in patients with ARI. The aim of this study is to determine the incidence of medication errors during the prescribing phase in patients ARI and the relationship between medication errors and age and number of courses of therapy. It was an observational analytical study with a cross-sectional design. Moreover, sampling was conducted by using accidental random sampling from April 2025 at the X Community Public Health Center. In addition, data were analyzed by using the Chi-square test and it was presented in tabular form. The characteristics of ARI patients are 39% male and 59.4% female, with a predominant age group of 34.3%. 83.3% of patients receive ≤ 4 courses of therapy. The incidence of medication errors is 82.3% which occurs in both administrative and pharmaceutical aspects. There is a relationship between the number of courses of therapy and medication errors (p-value <0.05) which shows that the number of therapy received by the patient is a factor in the incidence of medication errors. There is no relationship between age of the patients and medication errors (p-value >0.05). There is a relationship between the number of therapies and the incidence of medication errors. However, there is no relationship between age and the incidence of medication errors.